PENGARUH SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU DAN DAMPAKNYA PADA HASIL BELAJAR SISWA DI SMP N I SAMBAS - Hani Darmayanti; Ubabuddin Ubabuddin; Deni Irawan (CV. ADIBA ASIHA AMIRA, 2023)
This research departs from what researchers see in the field, especially from student learning outcomes which have decreased every year. From this, the question arises why this can happen, there are indeed many factors that influence student achievement outcomes, one of which is external factors, namely from teacher performance because as teachers we it is impossible to blame the students for that. The formulation of this problem is 1). Is there a significant influence between the principal's supervision on teacher performance at Sambas 1 Public Middle School? 2). Is there a significant influence between teacher performance on student learning outcomes at Sambas 1 Public Middle School? 3). Is there a significant influence between the principal's supervision on teacher performance and what impact does it have on student learning outcomes at Sambas 1 Public Middle School?. The results of this study can be concluded: 1) There is no significant effect of the supervision carried out by the principal on teachers in terms of advancing teacher performance in learning as evidenced by the sig value: 0.367 > 0.0r so that Ho is accepted and Ha is rejected. Ho: There is no significant influence from the supervision carried out by the principal on teachers in terms of advancing teacher performance. The results obtained in the data analysis obtained that only 2.9% had the effect of supervision on teacher performance and the remaining 97.1% was influenced by other variables. 2). There is no significant effect of teacher performance on student learning achievement, as evidenced by the sig value: 0.248 > 0.05; means that Ha is rejected and Ho is accepted. Ho: There is no significant effect of teacher performance on student achievement. As for the data analysis, it was found that only 2.9% had the effect of supervision on teacher performance and the rest was influenced by other variables. 3). There is no significant effect of the supervision carried out by the principal on teacher performance and has no impact on student achievement. This is evidenced by the results obtained in the path data analysis in the summary of the correlation coefficient, both the direct effect of supervision on learning achievement and the effect of supervision simultaneously with teacher performance on learning achievement, there is no probability value smaller than 0.05.